APO epsilon 4 is associated with enhanced in vivo innate immune responses in human subjects - Gale, Stephen C; Gao, Li; Mikacenic, Carmen; Coyle, Susette M; Rafaels, Nicholas; Murray Dudenkov, Tanda; Madenspacher, Jennifer H; Draper, David W; Ge, William; Aloor, Jim J; Azzam, Kathleen M; Lai, Lihua; et al. (Journal of allergy and clinical immunology, 2014)
Background The genetic determinants of the human innate immune response are poorly understood. Apolipoprotein (Apo) E, a lipid-trafficking protein that affects inflammation, has well-described wild-type ( epsilon 3) and disease-associated ( epsilon 2 and epsilon 4) alleles, but its connection to human innate immunity is undefined. Objective We sought to define the relationship of to the human innate immune response. Methods We evaluated in several functional models of the human innate immune response, including intravenous LPS challenge in human subjects, and assessed association to organ injury in patients with severe sepsis, a disease driven by dysregulated innate immunity. Results Whole blood from healthy / volunteers induced higher cytokine levels on stimulation with Toll-like receptor (TLR) 2, TLR4, or TLR5 ligands than blood from / patients, whereas TLR7/8 responses were similar. This was associated with increased lipid rafts in monocytes. By contrast, / and / serum neutralized LPS equivalently and supported similar LPS responses in -deficient macrophages, arguing against a differential role for secretory APOE4 protein. After intravenous LPS, patients had higher hyperthermia and plasma TNF- alpha levels and earlier plasma IL-6 than patients. APOE4-targeted replacement mice displayed enhanced hypothermia, plasma cytokines, and hepatic injury and altered splenic lymphocyte apoptosis after systemic LPS compared with APOE3 counterparts. In a cohort of 828 patients with severe sepsis, was associated with increased coagulation system failure among European American patients. Conclusions is a determinant of the human innate immune response to multiple TLR ligands and associates with altered patterns of organ injury in human sepsis.